Polycystic Ovary Syndrome Triggers Atrial Conduction Disorders: A Systematic Review and Meta-Analysis - Dimitrios V. Moysidis; Andreas S. Papazoglou; Christos Tsagkaris; Vasileios Oikonomou; Anna Loudovikou; Anastasios Kartas; Nikolaos Stalikas; Efstratios Karagiannidis; Mihnea-Alexandru Găman; Marios Papadakis; Chrysi Christodoulaki; Periklis Panagopoulos (MDPI AG, 2022)
Background: Polycystic ovary syndrome (PCOS) is closely related to various adverse cardiovascular manifestations and increased cardiovascular risk. However, atrial fibrillation (AF) development and atrial conduction abnormalities have not been thoroughly studied in patients with PCOS. Methods: This meta-analysis (CRD42021261375) was conducted in accordance with the PRISMA guidelines. Our aim was to investigate associations between PCOS and disorders in atrial conduction parameters linked with an increased risk for AF occurrence. Results: Five cohort studies with aggregate data on 406 adult women (229 with PCOS and 177 age-matched without PCOS) were included in this analysis. Our results showed a significantly increased mean difference in P-wave maximum duration (+7.63 ± 7.07 msec; p < 0.01) and P-wave dispersion (+11.42 ± 5.22 msec; p = 0.03) of patients with PCOS compared to healthy women. The mean difference in P-wave minimum duration (−2.22 ± 2.68 msec; p = 0.11) did not reach the statistical threshold between the compared groups. Echocardiographic measurements of atrial electromechanical delay (AED) also indicated a statistically significant mean difference in favour of the PCOS group in all assessed parameters, except for atrial electromechanical coupling (PA) in the tricuspid annulus. Particularly, PCOS was associated with increased lateral PA, septal PA, inter- and intra-AED durations (mean difference: +17.31 ± 9.02 msec; p < 0.01, +11.63 ± 7.42 msec; p < 0.01, +15.31 ± 9.18 msec; p < 0.01, +9.31 ± 6.85 msec; p < 0.01, respectively). Conclusions: PCOS is strongly associated with alterations in several electrocardiographic and echocardiographic parameters indicating abnormal atrial conduction. Therefore, PCOS could be considered as a causal or triggering factor of AF. Larger studies are needed to confirm these results and investigate direct associations between PCOS and AF.